2016
DOI: 10.1007/s00429-016-1339-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alexithymia and empathy on the neural processing of social and monetary rewards

Abstract: Empathy has been found to affect the neural processing of social and monetary rewards. Alexithymia, a subclinical condition showing a close inverse relationship with empathy is linked to dysfunctions of socio-emotional processing in the brain. Whether alexithymia alters the neural processing of rewards, which is currently unknown. Here, we investigated the influence of both alexithymia and empathy on reward processing using a social incentive delay (SID) task and a monetary incentive delay (MID) task in 45 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 79 publications
1
18
3
Order By: Relevance
“…In line with the findings reported above, the results of a recent fMRI study in our lab provided evidence for distinct effects of the alexithymia facets on the processing of rewards (Goerlich et al, 2017). While participants anticipated social rewards (anticipation phase), DIF scores correlated with activity in the subgenual and perigenual ACC and the adjacent ventromedial PFC.…”
Section: Functional Imagingsupporting
confidence: 88%
“…In line with the findings reported above, the results of a recent fMRI study in our lab provided evidence for distinct effects of the alexithymia facets on the processing of rewards (Goerlich et al, 2017). While participants anticipated social rewards (anticipation phase), DIF scores correlated with activity in the subgenual and perigenual ACC and the adjacent ventromedial PFC.…”
Section: Functional Imagingsupporting
confidence: 88%
“…monetary). One prominent hypothesis states that the anticipation and receipt of social incentives engages both a generalist neural network that consists of brain regions involved in the processing of incentives irrespective of their type (such as the basal ganglia), and a specialist network of regions specifically involved in the processing of social information (such as the temporoparietal junction, the dorsomedial prefrontal cortex, the precuneus, and the superior temporal gyrus) (Barman et al, 2015a;Goerlich et al, 2017a;Spreckelmeyer et al, 2013a). This hypothesis has been challenged though by at least two recent meta-analyses, the results of which were consistent with the idea that a general-purpose brain system is involved in the anticipation of incentives irrespective of their type.…”
Section: Brain Regions Involved In the Anticipation Of Social Rewardsmentioning
confidence: 99%
“…On the one hand, there is evidence that the processing of social incentives frequently evokes the activity of generic brain regions involved in reward prediction and value encoding, such as the striatum and the orbitofrontal cortex (Barman et al, 2015b;Rademacher et al, 2014;Spreckelmeyer et al, 2009). On the other hand, some studies have also suggested that the processing of social incentives might involve additional brain regions thought to be critical for socialcognitive processes, such as the temporoparietal junction, dorsomedial prefrontal cortex, precuneus, and superior temporal gyrus (Barman et al, 2015b;Goerlich et al, 2017b;Spreckelmeyer et al, 2013b). However, a clear picture of the brain circuits underpinning social reward and punishment processing in the human brain is still missing due to inconsistencies in the areas identified across individual studies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its significant role in social interaction, pain empathy has become an intense area of research in psychology and neuroscience ( Sassenrath et al, 2016 ; Yang et al, 2017 ). Recently, a large body of studies have investigated whether and how pain empathy is affected by social factors such as sense of fairness ( Singer et al, 2006 ), monetary reward ( Guo et al, 2012 ; Goerlich et al, 2016 ), affective preference ( Wang et al, 2014 ; Yang et al, 2014 ), social distance ( Zaki, 2014 ; Wang et al, 2016 ), as well as competition and cooperation ( Cui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%